2008
DOI: 10.1186/1476-4598-7-2
|View full text |Cite
|
Sign up to set email alerts
|

Sub-megabase resolution tiling (SMRT) array-based comparative genomic hybridization profiling reveals novel gains and losses of chromosomal regions in Hodgkin Lymphoma and Anaplastic Large Cell Lymphoma cell lines

Abstract: BackgroundHodgkin lymphoma (HL) and Anaplastic Large Cell Lymphoma (ALCL), are forms of malignant lymphoma defined by unique morphologic, immunophenotypic, genotypic, and clinical characteristics, but both overexpress CD30. We used sub-megabase resolution tiling (SMRT) array-based comparative genomic hybridization to screen HL-derived cell lines (KMH2 and L428) and ALCL cell lines (DEL and SR-786) in order to identify disease-associated gene copy number gains and losses.ResultsSignificant copy number gains and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 55 publications
(54 reference statements)
1
10
0
Order By: Relevance
“…15 The data of miRNA arrays, showing high expression of miR-182 and miR-183 in L428 and L1236 cell lines, 44 and high expression of miR-96 in HRS cells of EBV-negative nodular sclerosis cHL cases are also in agreement with our results. 44 Our data on FOXO1 copy number loss in cHL cell lines are in accordance with the previously described 13q13.1-q21.32 loss in L428 and KM-H2 cell lines 33 and the 13q loss in L1236 cells. 45 In SUP-HD1, we found a derivative chromosome 13 with interstitial deletion similar to previous observations.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…15 The data of miRNA arrays, showing high expression of miR-182 and miR-183 in L428 and L1236 cell lines, 44 and high expression of miR-96 in HRS cells of EBV-negative nodular sclerosis cHL cases are also in agreement with our results. 44 Our data on FOXO1 copy number loss in cHL cell lines are in accordance with the previously described 13q13.1-q21.32 loss in L428 and KM-H2 cell lines 33 and the 13q loss in L1236 cells. 45 In SUP-HD1, we found a derivative chromosome 13 with interstitial deletion similar to previous observations.…”
Section: Discussionsupporting
confidence: 75%
“…23,33,34 To specifically investigate copy number changes of the FOXO1 locus, we performed FISH on the cHL cell lines KM-H2, L428, L1236, SUP-HD1, and U-HO1. We identified an interstitial deletion of chromosome 13q involving FOXO1 in the diploid cell line SUP-HD1, whereas in the triploid cell lines KM-H2 and L1236, as well as in tetraploid L428, only 2 chromosomes 13 (harboring the FOXO1 locus) were present (supplemental Figure 3).…”
Section: Foxo1 Locus Is Often Deleted In Hrs Cells Of Chl and In Chl mentioning
confidence: 99%
“…In fact, ALCLs are characterized by a complex karyotype, different numerical and structural chromosomal abnormalities and chromosomal imbalances. [4][5][6][7][8][9] The JunB transcription factor has been shown to contribute to the pathogenesis of ALK-positive ALCLs 10 where its abnormally high accumulation is explained by at least two mechanisms: (i) increased JUNB transcription dependent on Erk1/2 kinase activation by NPM-ALK and (ii) increased JUNB translation mediated by mTOR activation by AKT, which is induced by NPM-ALK via activation of PI3K. However, how JunB promotes ALCL lymphomagenesis is still unclear.…”
Section: Introductionmentioning
confidence: 97%
“…It is ubiquitously expressed in normal human tissues and regulates gene transcription, cell cycle control and apoptosis (Nagashima et al, 2003). Distorted ING3 expression has been found in human head and neck squamous cell carcinomas (HNSCCs) and several lymphoma-derived cell lines (Gunduz et al, 2002(Gunduz et al, , 2008Fadlelmola et al, 2008). In melanoma cells, we have shown that ING3 promotes ultraviolet (UV)-induced apoptosis through the Fas/caspase-8-dependent pathway (Wang and Li, 2006).…”
Section: Introductionmentioning
confidence: 97%